Pengaruh Manajemen Kepala Sekolah dan Profesionalisme Guru terhadap Kinerja Guru di SMP IT Izzatuna Putra Putri Palembang - Zulaiha Amelia Perdana; Alhadi Yan Putra; Sri Wahyu Indrawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify and analyze: The influence of principal management on teacher performance; The influence of teacher professionalism on teacher performance; and The combined influence of principal management and teacher professionalism on teacher performance. This research is a quantitative study using partial correlation methods. The study was conducted at SMP IT Izzatuna Putra and Putri Palembang with 52 teacher respondents. Data collection techniques included questionnaires, observations, and documentation. Validity and reliability tests utilized internal validity and reliability measures. Prerequisite analysis tests included normality test, linearity test, and multicollinearity test, with data analyzed using simple regression and multiple regression techniques. The results showed that: there is a positive and significant influence of principal management on teacher performance with a correlation value of 2.013 and a relationship percentage of 0.2%; there is a positive and significant influence of teacher professionalism on teacher performance with a correlation value of 2.048 and a relationship percentage of 2.0%; and there is a positive and significant combined influence of principal management and teacher professionalism on teacher performance with a correlation value of 4.172 and a relationship percentage of 31.2%. In conclusion, the joint influence of principal management and teacher professionalism on teacher performance at Izzatuna Palembang IT Middle School. Keywords: Principal Management; Professionalism; Performance.